Military readiness : concepts, choices, consequences - Betts, Richard K., 1947- (Washington, D.C. : Brookings Institution, 1995)
In this book, strategy expert Richard K. Betts surveys problems in developing and measuring combat readiness before, during, and after the cold war. He analyzes why attempts to maximize it often have counterproductive effects, and how confusions in technical concepts cause political controversy.
The book explores conflicts between two objectives that are both vital but work against each other because they compete for resources: operational readiness to fight immediately, and structural readiness - the number of organized units that increase military power, but require time during a crisis to gear up for combat. Betts also discusses the problem brought on by the cold war and plunging defense budgets: mobilization readiness - the plans and arrangements needed to shorten the time for recreating a large military if it once again becomes necessary. Betts offers new ideas for understanding the dilemmas and tradeoffs that underlie debates on how readiness should be maintained in peacetime, and he explores the strategic consequences of different choices.
Pt. 1. Understanding Readiness. 1. The Warrant for Readiness: Blood, Treasure, and Time. 2. Readiness as a Stairway: The Linear Image. 3. Readiness as a Wave: The Cyclical Image -- Pt. 2. The Cold War. 4. Muddled Measurement: Lies, Damn Lies, and Readiness Statistics. 5. Readiness as a Political Football: Proclaiming Priorities and Evading Choices. 6. U.S. and Soviet Readiness: A Comparison -- Pt. 3. After the Cold War. 7. Readiness and Strategy after the Cold War. 8. Between Two Traditions: Mobilization Readiness -- Appendix: Linear and Cyclical Images.
Includes bibliographical references (p. 255-315) and index.
Keywords: Military readiness